Oscillatory Onset and Offset in Young Vocally Healthy Adults Across Various Measurement Methods - Patel, Rita R.; Walker, Reuben; Döllinger, Michael (Journal of Voice, 2017)
OBJECTIVE: This study aimed to investigate the relationship between (1) oscillatory onset-offset time across various approaches that use different measurement criteria and (2) oscillatory onset and offset times in vocally healthy young adults. METHOD: Oscillatory onset-offset times were obtained from 71 vocally normal adults, using high-speed videoendoscopy. Comparisons between the different onset methods involved measurement of the oscillatory onset time (OOT), voice initiation period (VIP), and the phonation onset time (POT), and for offset methods involved computation of the oscillatory offset time (OOToff) and the phonation offset time. RESULTS: Correlation of the OOT with the VIP was 0.240 (P = 0.04) and with the POT form glottal area waveform was 0.248 (P = 0.04); however, correlation between the VIP and the POT glottal area waveform was 0.661 (P < 0.001). For offset, there was a moderate correlation (rS = 0.503, P < 0.001) across OOToff and vocal offset period. The onset time was longest for the OOT followed by the VIP and the POT. There was no correlation between onset and offset for all methods. CONCLUSIONS: A framework for quantification of oscillatory onset-offset time was developed for /hi/ tasks, which can be used for future measurements of disordered voice. A positive relationship was observed between VIP and POT and between OOToff and vocal offset period. There was a nonlinear relationship between the OOT, VIP, and POT measures. Onset-offset times are strongly influenced by the calculation method used, the pros and cons of which are discussed in this paper. Vibratory onset and offset represent physiologically different phenomena.
EVALuna2:35531